Manejo integrado de la Broca del café (Hypothenemus hampei), en la Hacienda tres Hermanos, Cantón Ventanas Provincia de los Ríos. - Gavilánez Bravo, Jordán Krissman (2020)
Coffee production is one more item in Ecuador's economy, which generates sources of employment. Today the coffee sector is affected by various pests, especially by the coffee bit, taking into account that its control is difficult once it enters the fruit. Nowadays the use of chemical substances for the control of this pest has been much debated due to the great contamination that occurs due to the use of them, and there are various types of controls that can be carried out, such as biological control. One way to carry out good control is to set traps so that the pest falls into them before entering the fruit. This control measure is more efficient than chemical control. The attack form of this insect is once an adult, it passes from coffee to coffee, piercing it and penetrating the green or ripe fruit, reaching the center of the seed, depositing the eggs that will later become larvae that will destroy a large part of the seed.